Aerobic capacity and sprint velocity of Leagues I and IV football players - Michalczyk, M.; Klapcinska, B.; Poprzecki, S.; Jagsz, S.; Sadowska-Krepa, E.; Kimsa, E.; Kempa, K.; Chmura, J. (Biomedical Human Kinetics, 2010)
Study aim: To assess the aerobic capacity, sprint velocity and changes in biochemical variables in football players preparing for the spring round of matches. Material and methods: Football players from League I (n = 19) and League IV (n = 15) were subjected twice to a graded running tests at the beginning and at the end of the pre-season preparation period. The following variables were recorded: maximum running velocity (km/h), ‡O2max (ml/kg/min), pulmonary ventilation (VE), load at the lactate threshold (LT) expressed as the threshold velocity (LTV; km/h) or %‡O2max, activities of enzymes in plasma - creatine kinase (CK) and lactate dehydrogenase (LDH), concentrations of lactate (La), ammonia (NH3) and of glucose (Gl) in plasma. At the end of the study the players were also subjected to a 30-m sprint test. Results: In League I players, LT significantly (p<0.05) increased from 11.9 ± 0.8 (at the beginning) to 12.6 ± 0.7 km/h (at the end of the pre-season preparation period) and the maximum load - from 17.4 ± 0.9 to 18.3 ± 1.0 km/h, respectively. Also, the concentrations of NH3 and Gl significantly (p<0.05) increased and enzyme activities tended to increase (p<0.10) following the graded running test. Moreover, they attained significantly (p<0.05) higher velocity at the first 5 m of the 30-m sprint test than their League IV mates. Conclusions: The negligible differences between football players from Leagues I and IV in their aerobic capacity and speed abilities, and the marked distance from world elite players in those indices, call for substantial changes in training strategies and schedules.